Analysis of the role of transcription factors in enhancing drought tolerance in sugarcane (Saccharum spp.) - Mbambalala, Nelisa (Stellenbosch : Stellenbosch University, 2020)
Thesis (MScAgric)--Stellenbosch University, 2020.